1983
DOI: 10.1103/physrevlett.51.911
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Relaxation-Time Spectrum in a CuMn Spin-Glass

Abstract: SQUID magnetometry measurements on a CuMn spin-glass reveal that the zero-fieldcooled magnetization strongly depends on the time the sample is kept at constant temperature prior to the field application. This result is evidently at variance with the common belief that an equilibrium spin-glass state is quickly obtained after cooling in zero field. The nonequilibrium behavior, as reflected in the complex time dependence of dm/dlnt f is interpreted to arise from slow dynamics of the relaxation-time spectrum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
272
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 423 publications
(292 citation statements)
references
References 6 publications
19
272
0
1
Order By: Relevance
“…Data analysis was performed by classical FFT methods, and within the frequency range of the first experiments, it was found that the power spectrum was stable and related by FDT to the out-of-phase susceptibility. 4,5 At the same period, the strong non-stationarity of spin glasses was experimentally detected 6,7 and related later to equivalent properties of glassy polymers already investigated long time before. 8 Very soon too, the non-stationarity of the very low frequency magnetic noise power spectrum was detected, 4 showing that the behavior of these systems is quite different when looking on different timescales.…”
Section: Introductionmentioning
confidence: 77%
“…Data analysis was performed by classical FFT methods, and within the frequency range of the first experiments, it was found that the power spectrum was stable and related by FDT to the out-of-phase susceptibility. 4,5 At the same period, the strong non-stationarity of spin glasses was experimentally detected 6,7 and related later to equivalent properties of glassy polymers already investigated long time before. 8 Very soon too, the non-stationarity of the very low frequency magnetic noise power spectrum was detected, 4 showing that the behavior of these systems is quite different when looking on different timescales.…”
Section: Introductionmentioning
confidence: 77%
“…This is exactly a realization of the oscillator as a thermometer of Section II. From what we know from the time-scales of real spin-glasses [20,22], if the time after the quench is of the order of 10 minutes, and the period of the L-C circuit is of the order of the second, we are probing (at least partially) the aging regime: the temperature (defined as the average energy of the capacitor) should be different from the bath temperature. We believe that it would be interesting to return to the magnetization noise experiments [21] with the purpose of measuring the effective temperature: this would give us, for instance, useful insights into the nature of the spin-glass transition.…”
Section: Discussion Experimental Perspectives and Conclusionmentioning
confidence: 99%
“…This definition of the frequency-and waiting-time-dependent correlation C O (ω o , t w ) and out-ofphase susceptibility χ ′′ O (ω o , t w ) closely follows the actual experimental procedure for their measure: one considers a time window around t w consisting of a few cycles (so that phase and amplitude can be defined) and small enough respect to t w so that the measure is "as local as possible in time". In fact, these two quantities are standard in the experimental investigation of aging phenomena in spin-glasses [20][21][22].…”
Section: Frequency Dependent Thermometers That Measure Effectivementioning
confidence: 99%
“…dependence of the response of the system on the time in which it is perturbed. Aging effects [1] are a signature that the system is far from thermal equilibrium and consequently the fluctuation-dissipation theorem is not valid [2]. It has been realized quite recently that aging is indeed a solution of the off-equilibrium dynamics in some exactly solvable models [3,4].…”
mentioning
confidence: 99%